(untitled) (Gaceta Técnica, 2016)
The purpose of this research was to reveal, understand and interpret the meanings related to the mathematics learning produced through a virtual environment under blended format, given by ten third semester students of Computer Engineering at the school of science and Technology of the Lisandro Alvarado University. The research was based on the interpretive paradigm from the phenomenological-hermeneutic perspective. The technique of in-depth interview was used for data collection. The results lead to the configuration of the following categories: perception of mathematics in blended learning environments and generation of mathematical knowledge, which allowed the theoretical construction that permits the conception of mathematics learning in the fields of blended learning environments as a gradual process, where its demystification is relevant, incorporating virtual environments to support learning in the context of modernization of educational settings